Peranan Hukum Mempengaruhi Perilaku Manusia - Herawati, Herawati; Ambarini, Siti Nur; Sulistiawati, Sulistiawati; Nurlindawati, Nurlindawati; Yunita, Nita (Legalitas: Jurnal Hukum, 2025)
This article aims to find out and analyze the role of law in influencing human behavior in society. The research method uses a normative literature review. The function of law in a community group is to implement a social control mechanism that will clean the community from unwanted community garbage so that the law has a function to maintain the existence of a group. In addition, the function of law in society also gives us an idea that if the function of law in society does not run as it should, it will give rise to an arbitrary government, which in the end the government is no longer limited by law. The government will make itself the law itself. Like a dictatorial system of government. Therefore, the law must be implemented to become a social control in the life of society because the duties and functions of the law are not the goal